Cathepsin S (CTSS) activity in health and disease - A treasure trove of untapped clinical potential. (December 2022) - Smyth, Peter; Sasiwachirangkul, Jutharat; Williams, Rich; Scott, Christopher J.
Abstract: Amongst the lysosomal cysteine cathepsin family of proteases, cathepsin S (CTSS) holds particular interest due to distinctive properties including a normal restricted expression profile, inducible upregulation and activity at a broad pH range. Consequently, while CTSS is well-established as a member of the proteolytic cocktail within the lysosome, degrading unwanted and damaged proteins, it has increasingly been shown to mediate a number of distinct, more selective roles including antigen processing and antigen presentation, and cleavage of substrates both intra and extracellularly. Increasingly, aberrant CTSS expression has been demonstrated in a variety of conditions and disease states, marking it out as both a biomarker and potential therapeutic target. This review seeks to contextualise CTSS within the cysteine cathepsin family before providing an overview of the broad range of pathologies in which roles for CTSS have been identified. Additionally, current clinical progress towards specific inhibitors is detailed, updating the position of the field in exploiting this most unique of proteases.